Sustainable Exploitation from Aquifer of Shahrekord Plain Using the Various Scenarios - Rahim Alimohammadi Nafchi (Journal of Global Pharma Technology, 2017)
Human's insufficient information of its role that naturally played for the water cycle in nature (hydrologic cycle) and the set of these treats and performances are as main factors to divulge source of economic, environmental and social challenges at the different communities. Lack of appropriate use and comprehensive management of water resources in the catchments were caused that was made imbalance at the water balance in catchments and aquifers. In this regard, for implementing the integrated water resources management in the Jahanb in catchment and to avoid the negative performance and balance of Shahrekord plain, to protect and continuing of aquifer life and sustainable exploitation from it, this project was implemented at the Jahanbin catchment for two years. To analyze the situation of water resources in the future by predicting five scenarios from the method of water balance equation and using software Modflow, behavior and reaction of Shahrekord plain aquifer were used. The results indicate that the water balance of aquifer is always negative. Negative performance and reaction of aquifers has caused to be having a subsidence from 1976-1977to2013-2014that is 14.9 m. According to the conditions of 2013-2014, the results show that a subsidence in groundwater level will be in the short term (5-year in 2018) and the medium term (12-year in 2025) 17.8 and 43.4 m, respectively and the most of area tube wells will be dryin long-term (20-year in 2033). It should be noted that if a specific program was not carried out to manage water resources, it caused that catchment subsidence and finished the stored water of aquifer off.To prevent events as the subsidence, drying up wells, and unemployment of people and prevent the migration of residents, it needs to adhere to optimize water use and integrated water resources management in catchment by executive ruling and precise and intelligent control of water extractions in the Jahanbin catchment.Keywords: Jahanbin catchment and Shahrekord plain, Various scenarios, Sustainable and integrated water resources management, Water balance.